The politics of social protection in Eastern and Southern Africa - Hickey, Samuel; Lavers, Tom; Niño-Zarazúa, Miguel; Seekings, Jeremy (UNU-WIDER studies in development economics, 2021)
Why have so many countries in Africa adopted social protection programmes over the past decade? This text challenges the common assumption that this phenomenon has been entirely driven by international development agencies, instead focusing on the critical role of political dynamics within specific African countries.
Keywords: Public welfare : Political aspects : Africa; Social security : Political aspects : Africa